Isochronous cyclotron C-250 for proton therapy application - Alenitsky, Yu.G.; Vorozhtsov, S.B.; Glazov, A.A.; Zaplatin, N.L.; Kostromin, S.A.; Karamisheva, G.A.; Onischenko, L.M. (Національний науковий центр «Харківський фізико-технічний інститут» НАН України, 2010)
Project of C-250 – cyclotron for proton therapy is considered. Energy of the extracted form cyclotron beam was increased according to medical requirements up to 250 MeV. 4-fold and compact types of magnet yoke were studied by 3D computer magnetic field calculations. The ability of optimal combination of the magnet yoke, HF and extraction systems of the cyclotron based on the dynamics of the proton beam in calculated magnetic and accelerating field is under discussion. Dubna scientific medicine center is under development since 1967 on the base of the proton beam of LNP JINR Phazotron. Proton beam with energy Ер~170 MeV and intensity I~0.1 μA is used for patients irradiation. Proposal of the cyclotron with the same beam characteristics was published earlier.